Sumang Gayo as Stimulation of Moral Development in Early Childhood - Munawarah; Ikhsan; Muhammad Ghafur (JOYCED: Journal of Early Childhood Education, 2023)
Stimulation of early childhood development can be done in various ways. This includes the development of children's moral values ​​and character, which is currently decreasing, and the moral damage that occurs causes a negative impact on themselves and their environment. This study uses the Library Research Study. Data analysis in this study uses data reduction, data display, and conclusion. Research results show that there are four sumang that can stimulate the development of children's morals and character, namely: Sumang Penengonen (Vision), Sumang Pelangkahen (Running rules), Sumang Kenunulen (Sitting rules), Sumang Perceraken (Rules of speaking). The impact of sumang stimulation on children's moral development and character is that children understand better how to behave correctly, such as being polite and courteous. Children will have a character that cares about others. Children will have a gentle character. Increase children's self-awareness. Improve children's language skills. Children behave independently, have mutual respect for others, can solve problems, have a sense of responsibility, and can adapt to new people.